Analisis Putusan Pengadilan Negeri Surabaya No.746/Pdt.G/2021/PN.Sby Terkait Wanprestasi dalam Perjanjian Pengikatan Jual Beli Tanah di Kota Surabaya - Dhaniar Eka Budiastanti; Daniel Ananda Sebayang (Bhirawa Law Journal, 2026)
The practice of breach of contract in a Binding Sale and Purchase Agreement (PPJB) often leads to legal disputes that demonstrate a clash between legal certainty and the principle of utility. This research aims to analyze the inconsistency in the application of civil law norms in the Surabaya District Court Decision No. 746/Pdt.G/2021/PN.Sby, along with its juridical implications. This normative legal research employs a statutory approach, a case approach, and a conceptual approach. The collection of primary and secondary legal materials was conducted through library research, which were subsequently analyzed using a descriptive-analytical method. The results indicate that although the defendant was proven to have committed a breach of contract by failing to fulfill their obligations under the PPJB, the judge's considerations tended to emphasize the principle of utility to protect the bona fide purchaser, without providing proportional legal certainty for the plaintiff. The juridical implication of this decision is the emergence of obscure norms and weak legal certainty in the resolution of land PPJB disputes. The lack of synchronization between the Indonesian Civil Code and the Basic Agrarian Law causes ambiguity in the legal standing of the PPJB, thus potentially triggering new disputes in the future. Furthermore, legal protection for bona fide purchasers becomes suboptimal due to the absence of explicit regulations regarding the legal status of the PPJB and the limits of purchaser protection.